Paradise remade : the politics of culture and history in Hawaiʻi - Buck, Elizabeth Bentzel (Temple University Press, 1993)
This is a book about the politics of competing cultures and myths in a colonized nation. Relying on Althusserian Marxist theory, Elizabeth Buck considers the transformation of Hawaiian culture, with a focus on the indigenous population rather than on the colonizers. In Paradise Remade, the author reframes Hawaiian history, focusing on how Hawaii's established religious, social, political, and economic relationships have changed in the past two hundred years as a result of Western imperialism. This account of the politics of island culture and history is particularly timely in light of current Hawaiian demands for sovereignty one hundred years after the overthrow of the monarchy in 1893. Drawing on a wide range of critical theories of social structure and change, language and discourse, and practices of representation, Buck examines the social transformation of Hawaii from a complex hierarchical, oral society to an American state dominated by corporate tourism and its myths of paradise. She pays particular attention to how contemporary Hawaiians are challenging the use of their traditions as the basis for exoticized entertainments by establishing new institutions such as hula halau (schools) and the annual hula competition of the Merrie Monarch Festival to recover their history and culture. Buck demonstrates that sacred chants and hula were an integral part of Hawaiian social life; as the repository of the people's historical memory, chant and hula practices played a vital role in maintaining the links between religious, political, and economic relationships. As colonizers concentrated on transforming the economic and political organization of the islands and missionaries undertook conversion to Christianity, the suppression of these cultural practices became a key element in establishing European dominance. Tracing the ways in which Hawaiian culture has been variously constructed by Western explorers, New England missionaries, the tourist industry, ethnomusicologists, and contemporary Hawaiians, Buck offers a fascinating "rereading" of Hawaiian history.